Cheсklist of gastropod molluscs in mangroves of Khanh Hoa province, Vietnam - Zvonareva, Sofya; Kantor, Yuri (Zootaxa, 2016)
Gastropod molluscs are one of the most important components of mangrove ecosystem. Mangroves in Central Vietnam have a rather limited distribution due to peculiarities of the coastline morphology and presently their fauna remains understudied. Extensive surveys were conducted in both natural vegetation and artificial mangrove plantations in several localities in Nha Trang Bay from 2005 to 2015. In total 65 species of gastropod molluscs were found alive, 17 of which can be considered as predominantly mangrove-associated. An illustrated guide is provided, with short synonymies and data on ecology and distribution. The recorded molluscan diversity is compared with published data on mangrove gastropods in different regions of the Indo-Pacific. Total species number and the proportion of mangrove-associated species are similar to studied faunas in Hong Kong, Malaysia and Thailand, but the diversity is much lower than that of the mangal fauna of the Philippines.